Ecological alterations associated with Submarine Groundwater Discharge (SGD), utilising Stable Isotope Analysis (SIA) - Foley, Laura Judith (Trinity College (Dublin, Ireland). Department of Geography, 2014)
Research was conducted in three systems over two ecoregions to examine the ecological impacts associated with SGD. The potential applications of stable isotope analysis (SIA) in the field of SGD ecological research were investigated and some of the possible causative physicochemical agents of ecological change associated SGD were considered. Two study systems involved karst-channeled SGD (Ohios de Agua, an exposed oceanic rock pool platform in southern Portugal; and Kinvara bay, a sheltered, semi-enclosed bay on the west coast of Ireland). The third system was the sheltered, semi-enclosed Ria Formosa lagoon in southern Portugal, where diffuse SGD issues from a sandy beach face.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin